EVOLUTIONARY-CONSERVED ENHANCERS DIRECT REGION-SPECIFIC EXPRESSION OF THE MURINE HOXA-1 AND HOXA-2 LOCI IN BOTH MICE AND DROSOPHILA - Frasch, Manfred; Chen, XW; Lufkin, Thomas (Development, 1995)
The HOM-C/Hox complexes are an evolutionary related family of genes that have been shown to direct region-specific development of the animal body plan. We examined in transgenic mice the DNA regulatory elements that determine the temporal and spatially restricted expression of two of the earliest and most anteriorly expressed murine genes, Hoxa-1 and Hoxa-2, which are homologues of the labial and proboscipedia genes of Drosophila. In both mouse and Drosophila, these genes have been shown to play a critical role in head development. We identified three independent enhancers which direct distinct portions of the Hoxa-1 and Hoxa-2 expression domains during early murine embryogenesis. Two enhancers mediate hindbrain-specific expression, being active in either rhombomere 2, the most anterior rhombomere expressing Hoxa-2, or in rhombomere 4, a region where Hoxa-1 and Hoxa-2 have been shown to exert critical developmental roles. The third enhancer is essential for the most extensive expression domain of Hoxa-1 and contains a retinoic acid response element. Point mutations within the retinoic acid response element abolish expression in neuroepithelium caudal to rhombomere 4, supporting a natural role for endogenous retinoids in patterning of the hindbrain and spinal cord. Analysis of the murine Hoxa-2 rhombomere 2-specific enhancer in Drosophila embryos revealed a distinct expression domain within the arthropod head segments, which parallels the expression domain of the Hoxa-2 homologue proboscipedia. These results suggest an evolutionary conservation between HOM-C/Hox family members, which includes a conservation of certain DNA regulatory elements and possible regulatory cascades.
Keywords: TRANSGENIC; HOMEOBOX; DROSOPHILA; EVOLUTION; ENHANCER; RETINOIC ACID; HOXA-1